Implementation of the STEM-GeoGebra Integrated PjBL Model to Improve Student’s Critical Thinking Skills - Rohmah, Nurusy Syahrotir; Suryaningtyas, Wahyuni; Holisin, Iis (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2023)
The process of learning mathematics is in fact still not fully able to develop students' critical thinking skills. The importance of critical thinking for students lies in good problem solving methods. This study aims to describe students' critical thinking skills after implementing the STEM-GeoGebra integrated PjBL model and to find out students' responses. Students' critical thinking skills in learning mathematics are still low, as evidenced by the learning outcomes of students who have not yet reached the KKTP. A quantitative approach with the Pre-Experimental Designs One Group Pre-test Post-test design was used in this study. The target of this study-09 was class VII-C students of SMP Negeri 2 Surabaya for the 2022/2023 academic year with a total of 33 students. The method for implementing the STEM-GeoGebra integration PjBL model is carried out in 6 stages: 1) Problem recognition, 2) Project planning, 3) Developing project plans, 4) Evaluation of project progress, 5) Evaluation of project results, and 6) Evaluation of experiences. The instruments used were test questions and student response questionnaires that had been declared eligible for field tests by the validator. The study results show that students' critical thinking skills have increased, this is indicated by the large N-gain value of 0.42 in the medium category and the students' responses are in the good category with an average of 75. Furthermore, the results of this study indicate that there is an increase in critical thinking skills through the application of the STEM-GeoGebra integration PjBL model..